A caatinga dos biólogos e a política das plantas: controvérsias na transposição do Rio São Francisco - Brito, Eduardo Neves Rocha de (2017)
This dissertation originates from an ethnography of scientific activities at the São Francisco River transposition. Therefore, it is based on the theoretical-methodological processes coming from Bruno Latour’s Actor-Network Theory; a perspective engaged in the understanding and problematization of Science, State and non-human agencies. The data presented at first, is a product of the analysis of government documents, legal processes, technical reports and etc., in order to comprehend the places in which scientific controversies stand together with legal-normative conflicts that grant resources to the transposition. In a second moment, the data was built by fieldwork together with the scientists that rescue and monitor the caatinga plants degraded by the transposition. Since the immersion at documents enables the following of a socio-technical network in which science is historically linked to politics by answering directly to a developmental demand, the fieldwork shows the practices that make possible to see how science is a “policy in action”. Both of these methodological approaches are necessary to understand what kinds of knowledges, agents, discourses and ideals are mobilized in order for the caatinga plants to dialogue with state policies and legitimize, thus, an intervention that changes a portion of the flow of the waters of the biggest Brazilian river. Therefore, the idea is to show how scientific production registers the caatinga under recognizable aspects by the State and how following such register allows to clarify a very specific form of “nature management”